OCCUPANTS’ SATISFACTION OF SERVICED APARTMENTS DESIGN : CASE STUDIES IN KUALA LUMPUR - Keat, Ooi Wei; Bava Mohidin, Hazrina Haja (International Journal of Property Sciences (E-ISSN: 2229-8568), 2020)
This paper aims to identify the factors that affect a good serviced apartment design by looking at three (3) parameters which are physical attributes, social needs, and facilities and services through the occupants’ satisfaction levels. Despite the increasing number of serviced apartment developments in Malaysia, there has been limited research to analyse occupants’ wellness and satisfaction in a serviced apartment to generate a model to guide the service apartments’ design and development. The research is conducted using multiple case studies methods through physical observation and questionnaire surveys based on the three (3) parameters mentioned above at the golden triangle area of Kuala Lumpur among three case studies that have been identified. The findings reveal that occupants are generally satisfied with serviced apartments in Malaysia; however, various key components need to be reassessed and improved for future developments in order to serve as a reference for local authorities, developers, and designers to design serviced apartments in the local context from occupant’s perspective.